Peace and reconciliation in the classical world
1 online resource (ix, 208 pages)
Keywords: "Warfare has long been recognised as central to a proper understanding of the classical world, where, as the philosopher Heraclitus observed, war was 'both king and father of all.' More recently, however, an approach to the ancient world solely in such terms has been challenged. War was indeed pervasive, and was a prominent theme among poets and historians; but there was also a distinct value placed on peace, which might be understood not only as the absence of war but as an ideal to be imagined, instituted, and even imposed. This volume places peace at the centre of its concerns and explores classical ideas of peace as both an abstract concept the practical methods of conflict resolution"--Provided by publisher.